Production of presence : what meaning cannot convey - Gumbrecht, Hans Ulrich (Stanford University Press, 2004)
'Production of Presence' presents the thinking of Hans Ulrich Gumbrecht, one of the most consistently original literary critics of the 20th century. The text offers a personalized account of some of the central theoretical movements in literary studies and in the humanities over the past 30 years.